Water Scarcity And Climate Change: The Search For An Optimal And Sustainable Management - Abdelhafid, Aimar; Hana, Erabti (Université de M'sila, 2015)
Since the turn of the 20th century, water scarcity and climate change have become a major global issue as they affect national economies, human and animal lives and the environment. Growing demand for diminishing water resources and extreme climate events are posing serious challenges to governments worldwide in terms of sustainable development, food security and national stability. This paper raises and analyses a number of water issues with the aim of reaching a better understanding of water scarcity problems in the context of climate change. It seeks to suggest effective ways to face water scarcity and to deal with future risks of climate change. It sheds light on prominent cases and emphasizes the need for local, regional and international cooperation and coordination to cope with climate changes, raise water–use efficiency and sustain scarce water resources.
Keywords: Water scarcity, Climate change, Water-use efficiency, Sustainable management, Human security